2018
DOI: 10.1021/acs.energyfuels.8b02107
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Pore Types and Wettability of a Shale Gas Reservoir by Nuclear Magnetic Resonance: Longmaxi Formation, Sichuan Basin, China

Abstract: Reservoir properties, such as pore types and wettability, are essential for shale gas reservoir evaluation. However, advanced nuclear magnetic resonance (NMR), which has been routinely used in petrophysical characterization of reservoirs, is barely used to estimate these properties in shale gas reservoirs. In this study, several sets of specially designed NMR measurements, together with total organic carbon (TOC), X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), and contact angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Si–O can also interact with water molecules to produce silanol groups (Si–OH), and O-position silanol groups can be further dehydrated to form siloxane bonds (Si–O–Si), which are easily subjected to hydrophilic carboxylation, thus leading to the hydrophilicity of quartz. , Tabrizy et al, (2011) also considered that quartz is a hydrophilic mineral according to the isotherm morphology of quartz obtained from microcalorimetry experiments. In addition, under strong compaction, the contact types of rigid quartz particles are lines or points which protect some fractures and pores with clay to form a better connective water pathway , (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si–O can also interact with water molecules to produce silanol groups (Si–OH), and O-position silanol groups can be further dehydrated to form siloxane bonds (Si–O–Si), which are easily subjected to hydrophilic carboxylation, thus leading to the hydrophilicity of quartz. , Tabrizy et al, (2011) also considered that quartz is a hydrophilic mineral according to the isotherm morphology of quartz obtained from microcalorimetry experiments. In addition, under strong compaction, the contact types of rigid quartz particles are lines or points which protect some fractures and pores with clay to form a better connective water pathway , (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The organic pores are dispersed in the OM, which show ellipsoid or bubble shapes (Figure 4a), and the formation of OM shrinkage cracks are related to abnormal pressure during the hydrocarbon process 61 (Figure 4b). Oil more easily enters the organic pores and makes shale more oil wet.…”
Section: Calorimetry Experimentmentioning
confidence: 99%
“…Pore connectivity is mainly controlled by the developed organic and inorganic pores and the extent of their connection. 82 Wang et al 83 observed that oil-wet organic and water-wet inorganic pores jointly contribute to the macrowettability of Longmaxi gas shale, which was found to be mixed-wet based on the contact angle experiments. Tinni et al 84 used the sequential spontaneous imbibition of brine and dodecane to study pore network connectivity in shales using NMR.…”
Section: Effect Of the Pore Network On Shalementioning
confidence: 99%
“…Following eqs –, this ratio may therefore be expressed as which at a fixed NMR field strength depends only on the surface correlation times τ m and τ s and is independent of factors such as pore structure or the surface density of paramagnetic species . This metric is therefore considered a direct and noninvasive metric of molecular mobility within the adsorbed surface layer and has been extended elsewhere to the interpretation of wettability and adsorbate surface affinity (see e.g., refs ).…”
Section: Introductionmentioning
confidence: 99%